Peran Waktu Inokulasi Meloidogyne dalam Meningkatkan Infeksi Patogen Busuk Pangkal pada Bawang Putih - Budi Handayani; Hadi Wiyono; Subagya Subagya (Agrosains : Jurnal Penelitian Agronomi, 2013)
Basal rot was an important disease in garlic caused by Fusarium oxysporum f. sp. cepae (FOCe) and a major obstacle in garlic cultivation. Root knot nematodes (Meloidogyne) is endoparasitic nematodes causing plants become more susceptible to fungal pathogen infection. This research aimed to study the effect of double inoculation FOCe and Meloidogyne, and current inoculation against disease severity of basal root. The research was conducted through experimental procedures and prepared based on a randomized complete block design, with two factors consisting of three levels inoculation time. The first factor was FOCe and the second factor was Meloidogyne. The results showed that Meloidogyne presence could increase the disease severity of basal rot of garlic. Garlic was inoculated at 35 days after planting (dap) by Meloidogyne and FOCe cause the most severe disease of basal rot.